Humanistyka akademicka w dobie postnauki. Kilka uwag o filozofii reform szkolnictwa wyższego w Polsce - Wawrzynowicz, Andrzej (Człowiek i Społeczeństwo, 2021)
The aim of the paper is to discuss the current status of academic humanities (specifically philosophy) in the modern system of science and higher education. The recent structural reforms carried out in this sector in Poland had the ambitious goal of bringing the Polish universities in line with the current trends observed in academic education systems in developed countries, and improving the global competitiveness of Polish science. The article is an attempt at a critical confrontation of these strategic intentions with the actual effects achieved through the reforms, primarily in the context of the profound transformations of the very concept of science that has historically accompanied these changes. In particular, the paper presents a methodological analysis of the impact of the postulated new interpretation of research on the scientific status to date – and the prospects for further development – of traditional humanistic disciplines.